Essentials of ophthalmology - K., Dadapeer (Jaypee, 2015)
This book is written as comprehensive review for undergraduates and quick review for postgraduates. The book aims to present ophthalmology in a simplified, yet in a comprehensive manner covering all the topics with a lot of clinical photographs and illustrated diagrams.